Screening Indoor Threshold Levels of Carbon Monoxide (CO) Toxicity among Hospital Health Care Professionals in Sandstorm Ambient Air Pollution: Pulse CO-oximetry:Tehran-Iran;2011 - Agin, Kh; Khodabandeh, F; Moinazad-Tehrani, M (International Journal of Medical Toxicology and Forensic Medicine, 2013)
<!--[if gte mso 9]> <![endif]--> Background:Carbone’s monoxide is a poisoning gas and a pollutant of ambient air. Sandstorm is episodic dust-laden that reinforced CO toxicity levels in the environment. Hospital healthcare professionals are the first line healthy system organization and hospital workplace should be safe. The objective of this study was to determine the threshold levels of CO toxicity among hospital healthcare professionals in thesandstorm ambient air pollution through pulse CO-oximetry method. Method: Participations recruited base on the designed protocol and following inclusion and exclusion criteria. Results:A total of 117 subjects enrolled with means age ± SD; 38.97±9.03 years. It ranged between 20-60 years. Of those, 68 subjects was female and 49 male. Mean level of carboxyhemoglobin concentration (COHB %) was 2.52±3.40 SD,(P=0.03). 43% of sample study had CO toxicity upper than the normal set point. COHB% level noticeably increased in the female sex respect to male subgroups (χ =0.019). Conclusion:The resultant’s study was indicated particularity in female sex that a significant carboxyhemoglobin concentration found an above- normal set point level among target of population. As well as, threshold levels of CO toxicity in the workplace setting were noticeably high. Intervals of toxicity are nearby hazardous action level. The outcome of the study should be considered as an alarm for the public health program and presenting occult indoor CO poisoning.